Desenvolvimento de um protocolo para avaliação de bem-estar animal na produção de frangos de corte para obtenção de certificação - Alberto Junior, Francisco Willame de Sousa (2022)
The sector responsible for agriculture has production certifications, which are sought by the irresponsibility of agricultural production, already seeking a production whose production does not result in suffering to the people and free from threats that are the health issue. With the growth of safety guarantees for ensuring the comfort of animals, there is how to create a methodology for the maintenance of animal welfare applied to the promotion of animal safety, also accompanying animal welfare training, and the training of employees, the adequate qualifications, well-being conditions and their ambitious behaviours. To develop the training, which is delivered through a seal, was determined by the application of good animal welfare practices, were determined as animal welfare practices to successful ventures, evaluating themselves as being valuable to the property. each is suitable for functioning and that the animals are raised without physical, psychological or environmental discomfort. The result of the creation of its markets, which generates the opportunity for the producer to use the products sector, and the valorization of its national and international product with a differential in agriculture.